Effect of carbon nanotubes and silica nanoparticles on the durability of basalt fiber reinforced polymer composites in seawater and sea sand concrete environment. Issue 7 (15th April 2021) - Su, Chang; Wang, Xin; Ding, Lining; Wu, Zhishen
Abstract: This paper focuses on the durability of basalt fiber reinforced polymer (BFRP) laminas exposed to solutions of normal concrete (NC) and seawater sea sand concrete (SWSSC) by acceleration of temperature. Modification of BFRP laminas using different contents of silica nanoparticles and multiwall carbon nanotubes (MWCNTs) was conducted, and the effect of modification on the durability of the lamina was evaluated. The degradation and modification mechanism of BFRP laminas was investigated by scanning electron microscopy (SEM). The results showed that the BFRP laminas exhibited obvious strength degradation after exposure to the NC and SWSSC solutions, while the Young's modulus of the laminas remained nearly unchanged. The tensile strength of BFRP laminas in SWSSC solution declined faster than in NC solution due to the combined effect of alkali ions and saline ions in the SWSSC solution accelerated the corrosion of FRP. Additionally, the durability of MWCNT‐modified specimens has been significantly improved. The SEM images revealed that MWCNTs in the resin matrix improve the interface bonding performance between the fiber and the resin. Furthermore, the diffusion path of OH −, Cl −, and H2 O molecules is elongated and hindered by MWCNTs. The silica nanoparticle‐modified BFRP laminas obtained improved corrosion resistance performance only at a content of 1 wt%. Additionally, the long‐term residual tensile strength of modified BFRP laminas under NC and SWSSC environments was predicted. Abstract :